Fabrication and magnetoelectric investigation of flexible PVDF-TrFE/cobalt ferrite nanocomposite films - Bedanga Sapkota; Md Tanvir Hasan; Alix Martin; Rifat Mahbub; Jeffrey E Shield; Vijaya Rangari (Materials Research Express, 2022)
Flexible nanocomposite films, with cobalt ferrite nanoparticles (CFN) as the ferromagnetic component and polyvinylidene fluoride–trifluoroethylene (PVDF-TrFE) copolymer as the ferroelectric matrix, were fabricated using a blade coating technique. Nanocomposite films were prepared using a two-step process; the first process involves the synthesis of cobalt ferrite (CoFe _2 O _4 ) nanoparticles using a sonochemical method, and then incorporation of various weight percentages (0, 2.5, 5, and 10%) of cobalt ferrite nanoparticles into the PVDF-TrFE to form nanocomposites. The ferroelectric polar β phase of PVDF-TrFE was confirmed by x-ray diffraction (XRD). Thermal studies of films showed notable improvement in the thermal properties of the nanocomposite films with the incorporation of nanoparticles. The ferroelectric properties of the pure polymer/composite films were studied, showing a significant improvement of maximum polarization upon 5wt% CFN loading in PVDF-TrFE composite films compared to the PVDF-TrFE film. The magnetic properties of as-synthesized CFN and the polymer nanocomposites were studied, showing a magnetic saturation of 53.7 emu g ^−1 at room temperature, while 10% cobalt ferrite-(PVDF-TrFE) nanocomposite shows 27.6 emu/g. We also describe a process for fabricating high optical quality pure PVDF-TrFE and pinhole-free nanocomposite films. Finally, the mechanical studies revealed that the mechanical strength of the films increases up to 5 wt% loading of the nanoparticles in the copolymer matrix and then decreases. This signifies that the obtained films could be suited for flexible electronics.